Purification of lipase derived from Burkholderia pseudomallei with alcohol/salt-based aqueous two-phase systems - Ooi, Chien Wei; Tey, Beng Ti; Hii, Siew Ling; Mustapa Kamal, Siti Mazlina; Chi, John Wei Lan; Ariff, Arbakariya; Tau, Chuan Ling (Elsevier, 2009)
Alcohol/salt-based aqueous two-phase systems (ATPSs) were used to recover lipase derived from Burkholderia pseudomallei (B. pseudomallei). Nine biphasic systems, comprised of an alcohol-based top phase (ethanol, 2-propanol and 1-propanol) and a salt-based bottom phase (ammonium sulfate, potassium phosphate and sodium citrate), were evaluated for their effectiveness in lipase recovery. The stability of lipase in each of the solutions was tested, and phase diagrams were constructed for each system. The optimum partition efficiency for the purification of lipase was obtained in an ATPS of 16% (w/w) 2-propanol and 16% (w/w) phosphate in the presence of 4.5% (w/v) NaCl. The purified lipase had a purification factor of 13.5 and a yield of 99%.